2020
DOI: 10.3389/fpls.2019.01687
|View full text |Cite
|
Sign up to set email alerts
|

The Detection and Surveillance of Asian Citrus Psyllid (Diaphorina citri)—Associated Viruses in Florida Citrus Groves

Abstract: The plant pathogenic bacterium Candidatus Liberibacter asiaticus (CLas), the causal agent of the citrus disease Huanglongbing (HLB), and its insect vector, the Asian citrus psyllid (ACP; Diaphorina citri), have been devastating the Florida citrus industry. To restore the competitive production presence of Florida in the worldwide citrus market, effective and sustainable control of HLB and the ACP needs to be identified. As alternatives for resistance-inducing insecticides, viruses are currently being considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 54 publications
3
44
0
Order By: Relevance
“…Insect-specific viruses (ISVs) can offer potential biological alternatives as lethal and efficient viral vectors toward their respective invertebrate hosts ( 3 ). To identify ISVs of Florida ACP populations, high-throughput sequencing (HTS) was conducted on ACPs collected from Florida citrus groves ( 4 ). Subsequent bioinformatic analyses revealed the presence of sequences belonging to a novel reo-like virus with consistent closest protein similarity to the Cimodo virus (CMDV), a reovirus isolated from African mosquitoes ( 5 ).…”
Section: Announcementmentioning
confidence: 99%
See 1 more Smart Citation
“…Insect-specific viruses (ISVs) can offer potential biological alternatives as lethal and efficient viral vectors toward their respective invertebrate hosts ( 3 ). To identify ISVs of Florida ACP populations, high-throughput sequencing (HTS) was conducted on ACPs collected from Florida citrus groves ( 4 ). Subsequent bioinformatic analyses revealed the presence of sequences belonging to a novel reo-like virus with consistent closest protein similarity to the Cimodo virus (CMDV), a reovirus isolated from African mosquitoes ( 5 ).…”
Section: Announcementmentioning
confidence: 99%
“…HTS preparation for identification of this novel reo-like virus was previously described by Britt et al ( 4 ). Briefly, total RNAs were extracted using TRIzol reagent (Thermo Fisher Scientific, Waltham, MA, USA), according to the manufacturer’s instructions, from a pool of adult and nymph ACPs ( n = ∼30) that had been collected from Florida citrus groves in 2020.…”
Section: Announcementmentioning
confidence: 99%
“…Although many dsRNA molecules caused mortalities at a high dose, we selected only dsRNA molecules that exhibited dose response RNA interference. Because CTV is the most abundant virus in Florida citrus and is found where D. citri populations affect citrus (Britt et al, 2020) we engineered these molecules into attenuated CTV and expressed them in citrus leaves to protect against D. citri. We also report that targeting ETC membrane proteins by dsRNA in artificial diet is not as effective as targeting the soluble ETC subunit Rieske.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study revealed that CTV was the most abundant virus in Florida D. citri populations by high-throughput sequencing [58]. The results in this study indicate a high prevalence (40% to 100%) of CTV among D. citri collected from orchards.…”
Section: Discussionmentioning
confidence: 54%